2012
DOI: 10.1016/j.bbadis.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia induces atherosclerosis by NF-κB-dependent mechanisms

Abstract: Chronic intermittent hypoxia (CIH) causes atherosclerosis in mice fed a high cholesterol diet (HCD). The mechanisms by which CIH promotes atherosclerosis are incompletely understood. This study defined the mechanistic role of NF-κB pathway in CIH+HCD induced atherosclerosis. Wild type (WT) and mice deficient in the p50 subunit of NF-κB (p50-KO) were fed normal chow diet (ND) or HCD, and exposed to sham or CIH. Atherosclerotic lesions on the en face aortic preparation and cross-sections of aortic root were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Emerging evidence has revealed that the activation of NF-κB in the endothelium may contribute to the pathogenic process of atherosclerosis associated with IHR (8,9). NF-κB-mediated inflammatory pathways have integrated roles in classic atherosclerosis induced by a high-cholesterol diet (9). Patients with OSA have increased NF-κB activity in circulating neutrophils and monocytes, and elevated serum levels of NF-κB-dependent gene products (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has revealed that the activation of NF-κB in the endothelium may contribute to the pathogenic process of atherosclerosis associated with IHR (8,9). NF-κB-mediated inflammatory pathways have integrated roles in classic atherosclerosis induced by a high-cholesterol diet (9). Patients with OSA have increased NF-κB activity in circulating neutrophils and monocytes, and elevated serum levels of NF-κB-dependent gene products (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of NF-κB is controlled by the inhibitor of κB (I-κB), which retains NF-κB in the cytoplasm (7). Emerging evidence has revealed that the activation of NF-κB in the endothelium may contribute to the pathogenic process of atherosclerosis associated with IHR (8,9). NF-κB-mediated inflammatory pathways have integrated roles in classic atherosclerosis induced by a high-cholesterol diet (9).…”
Section: Introductionmentioning
confidence: 99%
“…While we did show that moderate OSA and AHI were associated with moderate DR and VTDR, we did not find any significant associations between mod OSA or AHI and DME. Chronic intermittent hypoxia is the major pathogenic feature of OSA that results in raised levels of vascular endothelial growth factor and other inflammatory cytokines that can contribute to DR progression [28][29][30]. The diagnosis and severity of OSA is based on the frequency of hypoxic episodes (apneas or hypopneas).…”
Section: Discussionmentioning
confidence: 99%
“…IH increased free cholesterol content in EC plasma membrane, likely by reducing gene expression of cholesterol efflux mediators ABCA1 and ABCG1, which may underlie the increased endocytosis of CD59. Mice deficient in the p50 subunit of NFκB on a high-cholesterol diet are protected from IH-induced ABCA1 inhibition and accelerated atherosclerosis, suggesting that ABCA1 and ABCG1 inhibition in IH may be mediated by NFκB activation (39). …”
Section: Discussionmentioning
confidence: 99%